Measuring disadvantage in the early years in the UK: a systematic scoping review. (November 2022) - Clery, Amanda; Grant, Claire; Harron, Katie; Bedford, Helen; Woodman, Jenny
Abstract: Background: The UK Government has a policy focus on the early years (children younger than 5 years old) as a timepoint to intervene and improve child health. However, implementation of interventions that reduce child health inequalities has not always been successful. One challenge lies in identifying appropriate target populations, which requires a better understanding of how disadvantage is used and measured in practice. We aimed to conceptualise disadvantage measured in child health literature and explore the associations between disadvantage and child health using these measures. Methods: We did a systematic scoping review to identify concepts of disadvantage used in empirical child health literature. We searched MEDLINE, Scopus, and grey literature for articles published in English between Jan 1, 2009, and Dec 7, 2020, for four key concepts: "disadvantage" and "child health outcomes" and "children under 5" and "United Kingdom". We included records if children younger than 5 years were studied, and associations between disadvantage and the child health outcomes of interest were reported. We excluded studies if they made comparisons between the UK and other countries, measured children as a whole population (0–18 years), or explored outcomes not of interest for the review. Findings: We extracted and analysed data from 86 studies. We developed a framework describing four key attributes conceptualising disadvantage: social, economic, individual-level, and area-level factors. Analysing the 16 studies that presented results for both individual-level and area-level factors separately, the majority (11 studies) found that individual-level measures of disadvantage identified stronger associations between disadvantage and child health than area-level measures. Interpretation: Our conceptual framework highlights to researchers, practitioners, and policy makers to carefully consider the disadvantage indicators used in the development, implementation, and evaluation of interventions aimed at reducing child health inequalities in the early years. Better access to individual-level disadvantage indicators in administrative data could further support these activities. Our study design identified a wide range of studies necessary to untangle disadvantage measured in the empirical literature, with considerable heterogeneity between studies. Further exploration of how disadvantage indicators are used in different contexts could provide additional evidence of target populations to reduce health inequalities. Funding: Child Health Research Charitable Incorporated Organisation PhD Studentship (award number 563654) and in part by the NIHR Great Ormond Street Hospital Biomedical Research Centre.